Capsaicinoids improve consequences of physical activity - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Erten, Fusun; Juturu, Vijaya (Elsevier Science Bv, 2018)
The purpose of this study was to investigate the effects of capsaicinoids (CAPs) on lipid metabolism, inflammation, antioxidant status and the changes in gene products involved in these metabolic functions in exercised rats. A total of 28 male Wistar albino rats were randomly divided into four groups (n = 7) (i) No exercise and no CAPs, (ii) No exercise + CAPs (iii) Regular exercise, (iv) Regular exercise + CAPs. Rats were administered as 0.2 mg capsaicinoids from 10 mg/kg BW/day Capsimax (R) daily for 8 weeks. A significant decrease in lactate and malondialdehyde (MDA) levels and increase in activities of antioxidant enzymes were observed in the combination of regular exercise and CAPs group (P < 0.0001). Regular exercise + CAPs treated rats had greater nuclear factor-E2-related factor-2 (Nrf2) and heme oxygenase-1 (HO-1) levels in muscle than regular exercise and no exercise rats (P < 0.001). Nevertheless, regular exercise + CAPs treated had lower nuclear factor kappa B (NF-kappa B) and IL-10 levels in muscle than regular exercise and control rats (P < 0.001). Muscle sterol regulatory element-binding protein 1c (SREBP-1c), liver X receptors (LXR), ATP citrate lyase (ACLY) and fatty acid synthase (FAS) levels in the regular exercise + CAPs group were lower than all groups (P < 0.05). However, muscle PPAR-gamma level was higher in the regular exercise and CAPs alone than the no exercise rats. These results suggest CAPs with regular exercise may enhance lipid metabolism by regulation of gene products involved in lipid and antioxidant metabolism including SREBP-1c, PPAR-gamma, and Nrf2 pathways in rats.
Keywords: Exercise; Capsaicinoid; PPAR-gamma; Nrf2; SREBP-1c